Drug-associated pulmonary arterial hypertension. (2nd September 2018) - McGee, Michael; Whitehead, Nicholas; Martin, Jennifer; Collins, Nicholas
Abstract: Introduction: While pulmonary arterial hypertension remains an uncommon diagnosis, various therapeutic agents are recognized as important associations. These agents are typically categorized into "definite", "likely", "possible", or "unlikely" to cause pulmonary arterial hypertension, based on the strength of evidence. Objective: This review will focus on those therapeutic agents where there is sufficient literature to adequately comment on the role of the agent in the pathogenesis of pulmonary arterial hypertension. Methods: A systematic search was conducted using PubMed covering the period September 1970– 2017. The search term utilized was "drug induced pulmonary hypertension". This resulted in the identification of 853 peer-reviewed articles including case reports. Each paper was then reviewed by the authors for its relevance. The majority of these papers (599) were excluded as they related to systemic hypertension, chronic obstructive pulmonary disease, human immunodeficiency virus, pulmonary fibrosis, alternate differential diagnosis, treatment, basic science, adverse effects of treatment, and pulmonary hypertension secondary to pulmonary embolism. Agents affecting serotonin metabolism (and related anorexigens): Anorexigens, such as aminorex, fenfluramine, benfluorex, phenylpropanolamine, and dexfenfluramine were the first class of medications recognized to cause pulmonary arterial hypertension. Although most of these medications have now been withdrawn worldwide, they remain important not only from a historical perspective, but because their impact on serotonin metabolism remains relevant. Selective serotonin reuptake inhibitors, tryptophan, and lithium, which affect serotonin metabolism, have also been implicated in the development of pulmonary arterial hypertension. Interferon and related medications: Interferon alfa and sofosbuvir have been linked to the development of pulmonary arterial hypertension in patients with other risk factors, such as human immunodeficiency virus co-infection. Antiviral therapies: Sofosbuvir has been associated with two cases of pulmonary artery hypertension in patients with multiple risk factors for its development. Its role in pathogenesis remains unclear. Small molecule tyrosine kinase inhibitors: Small molecule tyrosine kinase inhibitors represent a relatively new class of medications. Of these dasatinib has the strongest evidence in drug-induced pulmonary arterial hypertension, considered a recognized cause. Nilotinib, ponatinib, carfilzomib, and ruxolitinib are newer agents, which paradoxically have been linked to both cause and treatment for pulmonary arterial hypertension. Monoclonal antibodies and immune regulating medications: Several case reports have linked some monoclonal antibodies and immune modulating therapies to pulmonary arterial hypertension. There are no large series documenting an increased prevalence of pulmonary arterial hypertension complicating these agents; nonetheless, trastuzumab emtansine, rituximab, bevacizumab, cyclosporine, and leflunomide have all been implicated in case reports. Opioids and substances of abuse: Buprenorphine and cocaine have been identified as potential causes of pulmonary arterial hypertension. The mechanism by which this occurs is unclear. Tramadol has been demonstrated to cause severe, transient, and reversible pulmonary hypertension. Chemotherapeutic agents: Alkylating and alkylating-like agents, such as bleomycin, cyclophosphamide, and mitomycin have increased the risk of pulmonary veno-occlusive disease, which may be clinically indistinct from pulmonary arterial hypertension. Thalidomide and paclitaxel have also been implicated as potential causes. Miscellaneous medications: Protamine appears to be able to cause acute, reversible pulmonary hypertension when bound to heparin. Amiodarone is also capable of causing pulmonary hypertension by way of recognized side effects. Conclusions: Pulmonary arterial hypertension remains a rare diagnosis, with drug-induced causes even more uncommon, accounting for only 10.5% of cases in large registry series. Despite several agents being implicated in the development of PAH, the supportive evidence is typically limited, based on case series and observational data. Furthermore, even in the drugs with relatively strong associations, factors that predispose an individual to PAH have yet to be elucidated.